Effect of Sr-P Interaction on the Microstructure and Tensile Properties of A413.0 Type Alloys - A. M. Samuel; H. W. Doty; S. Valtierra; F. H. Samuel (Advances in Materials Science and Engineering)
The present study was performed on low magnesium A413.0 type alloys. The results show that strontium (Sr) is mainly concentrated in the silicon particles. Overmodification occurs when Sr precipitates in the form of Al2SrSi2, which takes place over a wide range of temperatures. The first peak occurs following the precipitation of α-Al, the second peak is merged with the precipitation of eutectic silicon (Si), and the third peak is a posteutectic reaction. Introduction of phosphorus (P) to Sr-modified alloys leads to the formation of (Al,P,Sr)2O5 compound, which reduces the modification effectiveness of Sr. Therefore, in the presence of P, the amount of added Sr should exceed 200 ppm. For the same levels of P, the tensile parameters of well modified alloys (233 ppm Sr) are relatively higher than those partially modified with Sr (about 60 ppm Sr) containing the same amount of P. During solution heat treatment, coarsening of the eutectic Si particles occurs by the growth of some particles at the expense of the dissolution of the smaller ones, as well as by the collision of nearby particles.